Dupilumab and alopecia: A Janus effect. Issue 5 (24th July 2019) - Patruno, Cataldo; Napolitano, Maddalena; Ferrillo, Maria; Fabbrocini, Gabriella
Abstract: Atopic dermatitis (AD) and alopecia areata (AA) are two common skin diseases that can coexist in the same patient, sharing some pathogenetic mechanisms such as the overexpression of interleukin 4 (IL4) and interleukin 13 (IL13). Recently, cases of AA healing during treatment with anti‐IL4/IL13 monoclonal antibody dupilumab (D) for AD were reported. However, cases of appearance of AA have been described during D treatment too. We report two patients that experienced these two opposite effects of D.